UTILIZATION OF AI ARTIFICIAL INTELLIGENCE IN THE DEVELOPMENT OF POETRY WRITING - Sukarto, Kasno Atmo (Prosiding Konferensi Internasional Kesusasteraan, 2025)
So far, the use of Artificial Intelligence, commonly called AI, is increasingly prominent among students, students, especially among literature students, and audiences who are in charge of literary issues, especially the development of poetry writing. Related to that, things that must be done both technically and strategically are to collaborate with the use of Artificial Intelligence (AI). The purpose of writing using the use of Artificial Intelligence (AI) in the development of poetry writing is the use of technology to facilitate human activities in helping information more effectively and efficiently. The research method applied in this writing is a descriptive-qualitative method, namely describing selected popular Indonesian literary works, especially poems that in their development utilize Artificial Intelligence. Related to this writing plan, the data source is taken from Kemaran: Anthology of Poetry published by the Indonesian Scholars-Literature Association (HISKI)) Komda DKI Jakarta in 2003. This poetry anthology gathers eight poetry writers who are members of HISKI Komda DKI Jakarta. Of the eight writers, "it is not a good and beautiful work". Therefore. themes that are randomly drawn. The themes to be described are taken as a sample from each author. The results of the analysis can be concluded that the use of Artificial Intelligence (AI) can be known for the development of poetry works in Kemarau: Anthology of Poetry, showing that there are shortcomings and weaknesses in the development of poetry creation, the location of weaknesses and shortcomings can be known. Thus, the use of Artificial Intelligence (AI) can help write poetry effectively and efficiently, especially for beginner writers, both students, students, and the community in charge of poetry writing problems.